(3ef dG jMVQI Gdabjgs - (3Gdbej, , GdTjN GdUOhb, GHf HGHhjg Gdbej, eMeO Hf Ydj Hf GdMSjf, J (B381(3g` (B991(3es ((3jYbhH Hf eMeO Ydj GdgRQGLQjHjs)
(3ChdgG (B:s
(3ChdgG(B: (3CHhGH GdbVGA hGdCMcGe, HGH ef jLhR GdJMGce Edjg hef dG jLhR, bGd CHh LYaQ (B... (3Qhi CMeO Hf YGFP Yf CHj NOjLI SGde (B... (3EjGce Cf jJMGce HYVce HYVG Edi Cgd GdLhQs
(3BNQgG (B:s
(3BNQgG(B: (3hQhi GdeYdi Hf eMeO GdHUQj (B... (3bGd GdfHj Udi Gddg Ydjg hSde(B: (3Ef YdjG Ydjg GdSdGe hUjJj hNdjaJj hRhLJg aGWeI SjOI GdfSGA fSGA GdYGdejf GHfJj (B... (3hGdMSf hGdMSjf Cgd HjJj hKbdj aGPgH Yfge GdQLS hWgQge JWgjQGs
(3jSHbgG fbhd U (B436 - 437s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 274s
(3GdPQjYI, L (B14: 58(3, L (B22: 146s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis